Pinacol Coupling of Aromatic Aldehydes using La-Ticl4 in CH3COOEt under Ultrasound Irradiation - Ji-Tai Li; Xue-Li Sun; Zhi-Ping Lin; Tong-Shuang Li (E-Journal of Chemistry)
Titanium tetrachloride can be reduced by lanthanum filings to the corresponding low valent titanium complex, which can induce some aromatic aldehydes to the corresponding pinacols in 28%-97% yields within 10-50 min in ethyl acetate at r.t. under ultrasound irradiation.